Effect of brick waste content on mechanical properties of mixed recycled concrete. (19th July 2021) - Liu, Xu; Wu, Jin; Zhao, Xing; Yan, Pengpeng; Ji, Weiyi
Highlights: The composition of mixed recycled coarse aggregate (MRCA) is complex. Recycled brick coarse aggregate (RBCA) is the weakest phase of MRCA. RBCA content influences the key properties of MRCA and MRCA concrete significantly. Abstract: The main compositions of recycled coarse aggregate produced from demolition waste of brick-concrete construction are recycled concrete coarse aggregate (RCCA) and recycled brick coarse aggregate (RBCA), called mixed recycled coarse aggregate (MRCA). This paper presents the results of test on the specific density (SD), saturated surface dry density (SSD), water absorption (WA), crushing value (CV) of twenty-three groups of MRCA and slump, SSD, cubic compressive strength ( fcu ), splitting tension strength ( fts ), static modulus of elasticity ( Ec ), flexural strength ( ff ) of the corresponding MRCA concretes. The results show that the correlation between WA of MRCA and RBCA content is the strongest, followed by SSD and WA of MRCA. A continuous decrease in SSD and a continuous increase in WA and CV can be observed with the increase of RBCA content, however, the SD has no obvious change with the increase of RBCA content when the SD is measured by drainage method. The cubic compressive strength and elastic modulus of MRCA concretes always decrease linearly with the increase of RBCA content, and the RBCA content has no obvious effect on the splitting tension and flexural strength in case the total amount of RCCA and RBCA is no more than 30%. According to the good correlation between the RBCA content and the properties of MRCA and MRCA concrete, the prediction model of WA, CV, and SSD of MRCA and fcu, Ec, and fts of MRCA concrete are established based on the RBCA content.